Air Pollution and Temperature in Seizures and Epilepsy: A Scoping Review of Epidemiological Studies - Rachit Sharma; Leah H. Schinasi; Brian K. Lee; Jennifer Weuve; Marc G. Weisskopf; Perry E. Sheffield; Jane E. Clougherty (Current Environmental Health Reports, 2024)
Purpose of the Review Seizures and epilepsy can be debilitating neurological conditions and have few known causes. Emerging evidence has highlighted the potential contribution of environmental exposures to the etiology of these conditions, possibly manifesting via neuroinflammation and increased oxidative stress in the brain. We conducted a scoping review of epidemiological literature linking air pollution and temperature exposures with incidence and acute aggravation of seizures and epilepsy. We systematically searched PubMed, Embase, Web of Science, and APA PsycINFO databases for peer-reviewed journal articles published in English from inception to February 7, 2024. Recent Findings We identified a total of 34 studies: 16 examined air pollution exposure, 12 ambient temperature, and six examined both air pollution and ambient temperature. Most studies were conducted in Asia (China, Taiwan, South Korea, and Japan). Nearly all studies retrospectively derived acute (daily average), ambient, and postnatal exposure estimates from ground monitoring systems and ascertained epilepsy cases or seizure events through record linkage with medical records, health registry systems, or insurance claims data. Commonly assessed exposures were particulate matter (PM 2.5 , PM 10 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), ozone (O 3 ), and daily mean ambient temperature. Overall, the main findings across studies lacked consistency, with mixed results reported for the associations of air pollutants and temperature metrics with both seizure incidence and acute aggravations of epilepsy.